Analysis of body and tail of a flapping drone / Chai Yuan - Chai, Yuan (2020)
The Micro Aerial Vehicle (MAV) is a kind of unmanned aerial vehicle with a small size, which has a unique performance that larger aircrafts do not have. MAV can fly in confined spaces and perform hover, forward flight, etc. The flapping wing micro aerial vehicle is one type of flight imitates the insects (birds), which can fly based on the flapping wing. Compared with fixed-wing aircraft, the flapping wing micro aerial vehicle (FWMAV) has a smaller volume, lighter weight, and higher flight efficiency. FWMAV can be largely used in military and civil applications. In this project, the flapping drone is a type of flapping wing micro aerial vehicle. The aerodynamic focus of the fuselage will move behind the center of gravity due to the effect of the tail. At the same time, the different angles of the tail surface will produce different moments to change the flight attitude of flapping drone and maintain a corresponding balance. Based on the research about the flying mechanism of birds and insects, this research project presented some aspects: the control of flying attitude, the angle between tail and body, the model of body and tail. An improved flapping drone model was designed according to the prototype, which includes some main components: wing, tail, fuselage, control system, mechanical structure. The effects of the different angle of the tail were tested under different inlet velocity. Moreover, we considered different pitch angles (from -45°to +45°) of the fuselage to simulate the real flying attitude based on the ANSYS method and actual experiment. After compared different conditions, the reasonable 20° tail angle was chosen in this project.